Analisis Fluktuasi Cadangan Devisa: studi kasus Indonesia, Vietnam, dan Malaysia - Dewi Mahrani Rangkuty; Rusiadi Rusiadi; Kiki Ramadhani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aims to analyze of fluctuations in foreign exchange reserves in three developing countries using time series data for the period 2000-2018 with the Research Method Of Panel Autoregressive Distributed Lag (ARDL). The results showed that foreign exchange reserves were the leading indicator in three developing countries (Indonesia, Vietnam, and Malaysia) but were unstable in the short run.  In the long and short term, significant variables affect fluctuations in foreign exchange reserves in three developing countries, namely exports and foreign debt. It is recommended to the Government to increase exports rather than imports to increase gold reserves which can later increase output towards economic growth.